Chemical composition and antibacterial properties of the essential oil of Pogostemon cablin - Aisyah, Yuliani; Hastuti, Pudji; Sastrohamidjojo, Hardjono; Hidayat, Chusnul (INDONESIAN JOURNAL OF PHARMACY, 2008)
The aim of this research were to evaluate the chemical compositions and antibacterial activities of patchouli. The identification of patchouli oil was carried out by using gas chromatography-mass spectrophotometer, fractionation of patchouli oil was done by vacuum fractionational distillation method. The gas chromatography mass spectra showed that the patchouli oil consisted of 15 components. It was found that the five major components were patchouli alcohol, Î-guaiene, Î±-guaiene, seychellene and Î±-patchoulene. Patchouli oil and high boiling point fraction exhibited antibacterial activity, while the low boiling point fractions did not show the antibacterial properties. The antibacterial properties found to be more effective for the Gram-positive bacteria than that the Gram-negative bacteria.Key words : patchouli oil, patchouli alcohol, fractinational distillation, antibacterial